1978
DOI: 10.1002/jcp.1040970320
|View full text |Cite
|
Sign up to set email alerts
|

Altered cyclic AMP‐dependent protein kinase activity in a mutant adrenocortical tumor cell line

Abstract: A somatic cell genetic approach has been used to evaluate the role of cyclic AMP-dependent protein kinase in ACTH action on adrenal steroidogenesis. A mutant clone, 8BrcAMPr-1, previously was isolated from a n ACTH-sensitive adrenocortical tumor cell line (clone Y1) following mutagenesis and selective growth in 8-bromoadenosine 3', 5'-monophosphate. This study demonstrates that the 8BrcAMPr-1 cells have an altered cyclic AMPdependent protein kinase. The protein kinase in the cytosol of the mutant characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Similar findings have been reported in neuroblastoma (27), Y1 adrenocortical (14), macrophage-like (25), and Chinese hamster ovary (28) cell lines. Only one Bt2cAMP-resistant S49 variant that does not affect cA-PK has been characterized (30).…”
supporting
confidence: 87%
“…Similar findings have been reported in neuroblastoma (27), Y1 adrenocortical (14), macrophage-like (25), and Chinese hamster ovary (28) cell lines. Only one Bt2cAMP-resistant S49 variant that does not affect cA-PK has been characterized (30).…”
supporting
confidence: 87%
“…We observed that an increase in cAMP content (and activation of PKA (7,23)) triggers the rapid (Յ1 min) and selective dephosphorylation of tyrosine residues on paxillin in Y1 cells. The dephosphorylation reaction precedes depletion of paxillin from focal adhesions, disassembly of adhesion plaques, dissolution of stress fibers, and rearrangement of the actin cytoskeleton.…”
Section: Camp Regulates Paxillin Dephosphorylation and Cell Shapementioning
confidence: 81%
“…The basis for this divergence, however, is not clear. The defects in the mutant Kin-i and clones likely are in the type I regulatory subunit of the cyclic AMP-dependent protein kinase (23,36). The natures of the mutations in the other Kin clones have not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The Y6 cell line is a spontaneous variant of the original Y1 cell line (25). Y1(Kin) and Y1(Cyc) mutants were obtained after mutagenesis with ethyl methanesulfonate or N-methyl-N'-nitro-N-nitrosoguanidine, followed by selection in 0.8 mM 8-bromoadenosine 3',5'-monophosphate (8BrcAMP) as described (22)(23)(24). Routine aspects of cell culture have been described elsewhere (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation